Development of a set of indicators for the quality of chronic pain management in Chinese community-dwelling older adults: a Delphi study - Xiaoyan Li; Jihua Zou; Qiying Hu; Rui Li; Jingquan Gao; Linyan Xu; Jiajia Chen; Yingge Tong; Yubin Chen (BMC Geriatrics)
Abstract Background Standardized and systematic quality assessments of chronic pain management, particularly among older adult populations, are lacking in resource-limited community settings. A specific set of indicators to evaluate the quality of chronic pain management in this population has yet to be developed. Therefore, the present study constructed a set of indicators to assess the quality of chronic pain management in Chinese community-dwelling older adults, providing a standardized reference and guidance for community health centers to manage chronic pain in this population. Methods The indicator set was developed in three steps. Step 1 involved preparation by forming a research team and establishing the guiding theory. Step 2 included developing an expert inquiry questionnaire based on a literature review and semi-structured interviews. Step 3 completed the construction of the indicator set through the Delphi method and hierarchical analysis to quantify the relative importance of each indicator and ensure the development of a scientifically validated and practically applicable evaluation model. Results The final set of indicators for evaluating the quality of chronic pain management among community-dwelling older adults in China comprised three primary indicators: structural quality indicator, process quality indicator, and outcome quality indicator. Structural quality indicators included 3 secondary and 11 tertiary indicators; process quality indicators included 4 secondary and 21 tertiary indicators; and outcome quality indicators included 2 secondary and 4 tertiary indicators. Across two rounds of questionnaires, the response rate was 100%, with expert authority coefficients of 0.924 and 0.938, coefficients of variation ranging from 0 to 0.32 and 0 to 0.20, and Kendall’s concordance coefficients of 0.302 and 0.220, respectively. Hierarchical analysis showed that the consistency ratios of all indicators were < 0.1000, indicating a balanced distribution of indicator weights. Conclusions This study introduces a preliminary framework, based on the “Structure-Process-Outcome” theory, to evaluate chronic pain management in Chinese community-dwelling older adults. Its reliance on expert opinions without empirical validation, exclusion of patient perspectives, and focus on Chinese communities limit its applicability and generalizability. Future research should address these limitations by incorporating patient feedback, empirically validating indicators, and evaluating their applicability across diverse populations.